Multivariate analysis of the exact effects of scalar position and insertion angle on speech discrimination - Rainer L. Beck; Antje Aschendorff; Susan Arndt; Manuel C. Ketterer (Frontiers in Neurology)
ObjectiveSeveral studies examined the influence of cochlear morphology on scalar position of the electrode array and rate of dislocation. Furthermore, researchers described better speech discrimination for patients with electrode arrays positioned in scala tympani but in small study cohorts. The aim of this study is to examine the exact impact of scalar position, dislocation and angular insertion depth on postoperative speech perception.DesignWe identified the patients (n = 531) implanted between 2003 and 2018 with a Contour Advance electrode array (CochlearTM) inserted via cochleostomy by a retrospective review of the Cochlear Implant Database and analyzed the postoperative imaging by cone beam computed tomography and the audiological protocol via a multivariate nonparametric analysis.ResultsThe multivariate nonparametric analysis of this study shows, that the dislocation of the electrode array and the insertion angle leads to no significant different postoperative speech discrimination results. Nevertheless, we could calculate a statistically significant amount of reduced speech recognition for monosyllables for primary scala tympani vs. scala vestibuli insertions (7.6%).ConclusionThis study, based on one of the largest study cohorts published to date, demonstrates reduced speech recognition for scala vestibuli insertions compared to scala tympani insertions. Insertion into the scala vestibuli results in a 7.6% decrease in speech discrimination for monosyllables.